Design of a New LC VCO using Active Inductor - Taghizadeh, Saeid; Taghizadeh, Maryam; Taghizadeh, Parisa; Kamaly, Abbas; Emamghorashi, Seyed Ali (International Journal of Computer Sciences and Engineering, 2025)
In this paper, a novel differential LC voltage-controlled oscillator (VCO) is presented. The VCO is based on the gm-boosted structure to relax the oscillation start-up current requirement and reduce the DC power consumption in comparison to conventional Colpitts structures. In the proposed VCO, a tunable active inductor is utilized as a part of LC tank instead of passive inductor with constant inductance. The proposed VCO is designed and simulated in ADS in a 0.18μm CMOS process. Simulation results indicate that the proposed VCO has a wide tuning range in comparison to other reported designs while consumes less DC power.